Perbandingan Tingkat Literasi Siswa SMAN 32 Jakarta Pra dan Pasca Pandemi - Alya Seiyra; Alysha Rawnie Aulia; Ghifary Adhyaksa; Muhammad Gianflo Deyang F.B; Najwa Liviya Novalina; Neha Najla Aura Nisri; Wikasita Laras Purudita; Rahmi Yulia Ningsih; Oki Hermawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the impact of the Covid-19 pandemic on the literacy levels of Indonesian students, with a focus on changes in reading habits and the application of literacy in daily life. The methodology used in this research is a descriptive approach combining both quantitative and qualitative methods. Data were collected through questionnaires and interviews, which were analyzed to measure students' literacy interest levels and to understand their views on literacy. The results show that the pandemic has led to a significant decline in students' reading habits, caused by factors such as online learning, digital fatigue, limited access to reading materials, and increased use of social media. To address this, it is recommended to provide broader access to reading materials and create an environment that supports literacy, both at school and at home.